Odpowiedź :
[tex]a. \\\\2x^2(x^3-3x^2+7x+2)=2x^2*x^3+2x^2*(-3x^2)+2x^2*7x+2x^2*2=2x^5-6x^4+14x^4+4x^2\\\\\text{Wspolczynnik przy najwyzszej potedze: } 2\\\text{Wyraz wolny: } 0[/tex]
[tex]b. \\\\(x+2)(4x^2-3x+4)=x*4x^2+x*(-3x)+x*4+2*4x^2+2*(-3x)+2*4=4x^3-3x^2+4x+8x^2-6x+8=4x^3+5x^2-2x+8\\\\\text{Wspolczynnik przy najwyzszej potedze: } 4\\\text{Wyraz wolny: } 8[/tex]
[tex]c. \\\\(6-3x^2-2x^3)(x^3-4)=6*x^3+6*(-4)-3x^2*x^3-3x^2*(-4)-2x^3*x^3-2x^3*(-4)=6x^3-24-3x^5+12x^2-2x^6+8x^3=-2x^6-3x^5+14x^3+12x^2-24\\\\\text{Wspolczynnik przy najwyzszej potedze: } -2\\\text{Wyraz wolny: } -24[/tex]